KELIMPAHAN DAN PERTUMBUHAN KERANG KEPAH (Meretrix meretrix) DI PERAIRAN ESTUARI SUAKA MARGASATWA KARANG GADING KABUPATEN DELI SERDANG - YUSNI AS ARI SIMANULLANG; Ipanna Enggar Susetya (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
This study aims to analyze the abundance of Shellfish in estuary waters of Karang Gading Wildlife Reserve of Deli Serdang Regency, to analyze the growth pattern and condition factors of Shellfish through the analysis of long-term relationship, and to analyze the relationship of abundance of Shellfish with estuary chemical physics chemistry of Karang Gading Wildlife Refuge Deli Serdang. Sampling of Shellfish was done in December 2017 - February 2018 in estuary waters of Karang Gading Wildlife Reserve of Deli Serdang Regency. The analysis for the substrate fraction was done in the Agronomy Laboratory of the Faculty of Agriculture, University of North Sumatra. Sampling of shellfish using claws of iron material having a volume of 0.0495m3. Sampling of shellfish is done once a month starting at 14.00 WIB - 18.00 WIB. The shellfish (Meretrix meretrix) obtained at each station was calculated by the number of individuals, measured by the width of the body shell and body weight, then analyzed which consisted of abundance, distribution, growth pattern, and condition factor. Measurements of physical-chemical water parameters are done directly in the field. The result of this research concludes that the most shell of abundance at station I with 694 ind / m2 value, the distribution of shellfish is classified into uniform distribution pattern. The pattern of growth of shellfish in each of its stations in estuary waters of Karang Gading Wildlife Reserve is negative allometrik. The condition factor of mangrove crab in each station morphologically has good hair.Kata Kunci: Kelimpahan, estuari, pola pertumbuhan, Meretrix meretrix